1986
DOI: 10.1111/j.1469-8137.1986.tb02887.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Proteins in the Nitrogen Nutrition of Ectomycorrhizal Plants

Abstract: SUMMARY f !The ability of mycorrhizal (M) and non-mycorrhizal (NM) plants of Pinus contorta (Dougl. ex Loud) to utilize protein as a nitrogen source was examined. Mycorrhizas were synthesized with the fungal symbionts PaxiUus involutus, Rhizopogon roseolus, Suillus bovinus and Pisoiithus tinctorius. The plants were grown under aseptic conditions and provided with nitrogen in the form of either protein or ammonium.Dry weight yields of plants infected with P. involutus, R. roseolus and S. bovinus were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(58 citation statements)
references
References 25 publications
2
55
1
Order By: Relevance
“…Extracellular protease activin-has been demonstrated in an ericoid and in a few ectomycorrhizal fungi (Leake & Read, 1990;Zhu et al, 1994). Indirect evidence of ectomycorrhizal protease production was also obtained in the experiments of Ahuzinadah, Finlay & Read (1986) and Ahuzinadah & Read (1986).…”
Section: Discussionmentioning
confidence: 55%
“…Extracellular protease activin-has been demonstrated in an ericoid and in a few ectomycorrhizal fungi (Leake & Read, 1990;Zhu et al, 1994). Indirect evidence of ectomycorrhizal protease production was also obtained in the experiments of Ahuzinadah, Finlay & Read (1986) and Ahuzinadah & Read (1986).…”
Section: Discussionmentioning
confidence: 55%
“…As the transfer in the other direction was very slow, there was a net capture of P by the mycorrhizal fungi. Abuzinadah et al (1986) emphasized the importance of microbial biomass as a major source of organic N for mycorrhizal plants. The same idea is presented by Leake & Read (1997), who point out that, since microbial biomass is more easily degradable than most plant litter, the rapid turnover of the microbial nutrient pool could make it a more important source of organic nutrients than plant litter, despite the much larger size of the total plant litter nutrient pool.…”
Section: mentioning
confidence: 99%
“…The proteolytic capability of P. involutus in pure culture is strongly influenced by pH. However the pH optimum varies substantially according to substrate (Abuzinadah & Read, 1986 a;Bending & Read, 1995). The uptake of amino acids by the P. involutus strain used in the present study was shown to be strongly influenced by pH (Chalot et al, 1995).…”
Section: Discussionmentioning
confidence: 78%
“…It is also possible that P. involutus accumulates N in the mycelium under some circumstances. It has been observed that Pinus contorta and Betula pendula plants inoculated with P. involutus can show lower uptake of NH^""" than non-mycorrhizal plants, a phenomenon which was not found with some other ectomycorrhizal fungi (Abuzinadah et al, 1986;Abuzinadah & Read, 1989a, b). These authors proposed that P. involutus might accumulate N in the mycelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation